Pornography Cybercrime in the Qatari Cybercrime Law - Alkrimeen, Ayman (2019)
This study deals with pornography cybercrime as organized by the Qatari legislator in the combating cybercrime law No. (14) of 2014, Where the law refers to pornographic crimes related to persons who have not reached the age of eighteen years of age under article (7) thereof, the researcher concluded that the Qatari legislator did not indicate what electronic pornography crime is and its concept accurately, in addition, it does not address pornographic crimes related to the promotion of prostitution, as well as the technical legal aspect of this type of crime. This study concluded with a series of conclusions and recommendations that were a natural secretion of the research process in this subject and the related concerns, taking into account the issue of the use of computers and various means in rationing those crimes. Key words: Crime, Cybercrime, Pornography Cybercrime, Child Pornography DOI: 10.7176/JLPG/87-23 Publication date:July 31st 201